Free functional gracilis muscle transfer in children with severe sequelae from obstetric brachial plexus palsy - Bahm, Jörg; Ocampo-Pavez, Claudia (Journal of Brachial Plexus and Peripheral Nerve Injury, 2008)
We present 4 children between 6 and 13 years suffering from severe sequelae after a total obstetric brachial plexus lesion resulting in a hand without functional active long finger flexion. They had successfully reanimated long finger flexion using a free functional gracilis muscle transfer. These children initially presented a total obstetric brachial plexus palsy without neurotisation of the lower trunk in an early microsurgical nerve reconstruction procedure.We describe our indications for this complex microsurgical procedure, the surgical technique and the outcome.